Current best practice for disease activity assessment in IBD - Walsh, A; Bryant, R; Travis, S (Nature Publishing Group, 2016)
Therapeutic advances in the management of IBD have led to a paradigm shift in the assessment of IBD disease activity. Beyond clinical remission, objective assessment of inflammation is now critical to guiding subsequent therapy as part of a 'treat to target' strategy. Multiple domains of disease activity assessment in IBD exist, each of which has its merits, although none are perfect. The aim of this Review is to comprehensively evaluate measures of disease activity in both ulcerative colitis and Crohn's disease, including clinical, endoscopic, histological and radiological assessment tools, as well as the use of biomarkers and quality of life evaluation. A subjective appraisal of the best indices for use in clinical practice is provided, based on index validation, responsiveness and experience in clinical trials, international specialist opinion, and practicality and suitability for use in clinical practice. This Review aims to enable the reader to gain confidence in IBD disease activity assessment and to give ready access to the necessary tools.